Pengaruh Penggunaan Bahasa Gaul di Kalangan Mahasiswa PGSD Universitas PGRI Delta Sidoarjo - Hendikus Sikone (PRODI PGSD UNIVERSITAS PGRI DELTA, 2024)
This article discusses the phenomenon of using slang language among Elementary School Teacher Education (PGSD) students at Universitas PGRI Delta Sidoarjo and its impact on the Indonesian language. In the context of globalization and the development of information technology, the use of slang language increasingly affects the use of the Indonesian language. This research uses a qualitative method to explore students' perceptions of slang language and its impact on linguistic identity and language diversity. The results show that the use of slang language can influence students' character, proficiency in Indonesian language, and the existence of Indonesian as the national language. With a deeper understanding of this phenomenon, it is hoped that this article can provide valuable insights in preserving the Indonesian language in academic and societal settings.